Micro-edm for micro-channel fabrication on nonconductive ZrO2 ceramic - Sabur, Abdus; Ali, Mohammad Yeakub; Maleque, Md. Abdul; Moudood, Abdul (Universiti Malaysia Pahang, 2014)
In this study, microelectro-discharge (micro-ED) milling of nonconductive ZrO2ceramicsis investigated using a Cu tool electrode in kerosene dielectric. An adhesive Cu foil is firmly attached on the workpiece to initiate the sparks. After the machining of Cu foil, an electrically conductive carbonic layer is formed on the ceramic workpiece disassociating the kerosene dielectric, which allows micro-ED milling to be continued on ZrO2.A micro-channel of 1500 μm length, 920 μm width and 150 μm depth is created. Energy-dispersive X-ray spectroscopy showed evidence of higher C precedence on the workpiece surface, which is the main element of the carbonic layer. It is shown that material removal rate increases with the increase of capacitance and voltage initially but it decreases at higher values. MRR and average surface roughness of the micro-channel are found to be 1.29×10-5 mm3/s and 0.25 μm, respectively, when machined with a capacitance of 0.1 nF and voltage of 80 V. This study shows that micro-ED milling is applicable for creating micro-channels on nonconductive ZrO2 ceramic with the assisting electrode technique.